Paternal investment and low birth weight – The mediating role of parity - Merklinger-Gruchala, Anna (PLoS One, 2019)
According to life-history theory, paternal investment affects the well-being of offspring. We hypothesized that environmental stress caused by a lack of paternal investment may diminish maternal resource allocation during pregnancy, especially for women who already have dependent children. Our study was conducted on a representative group of more than 80,500 singleton, live-born, full-term infants born in Krakow, Poland in the period 1995–2009. Birth data were obtained from the birth registry. We found that missing data about fathers (a proxy measure of low paternal investment) was associated with higher probability of multiparous mothers giving birth to low-birth-weight infants (1.48; 95% CI 1.05–2.08), but this was not the case with primiparous mothers (1.19; 95% CI 0.89–1.59). The statistically significant synergistic effect between parity and paternal investment was found (Synergy Factor = 2.12; 95% CI 1.47–3.05, p<0.001). These findings suggest that in situations of low paternal investment, multiparous mothers face trade-offs between investing in existing versus unborn children, therefore investment in the latter is lower. Such a strategy may benefit maternal fitness due to investment in older children, who have higher reproductive value.